Feasibility of Cross-well Seismic as CO2 Monitoring Tool - Shulakova, V.; Pevzner, Roman; Gurevich, Boris; Madadi, Mahyar; Bona, Andrej; Urosevic, Milovan (2015)
The next stage of CO2CRC Otway project involves exploration of the ability of various CO2 geosequestration techniques, including cross-hole seismic, to detect and monitor presence of CO2. Despite the limited spatial coverage of a cross-well survey, the acquired data could be used to improve reliability of the whole monitoring and verification program. Prior to any field experiment we evaluate the feasibility of cross-well seismic using computer modelling. We utilize finite-difference time-domain (FDTD) method for pre- and post- injection stages. Here we present the results of our study and validate the detectability of CO2/CH4 gas mixture on time-lapse cross-well seismic data on the direct as well as the reflected wave fields. We demonstrate that the presence of 15,000 t of a gas plume can lead to changes in transit times of up to 1.4 ms (in cross-well setting). The computed seismic tomography detects the difference in velocities up to 80 m/s. The difference caused by gas is also detectable in the migrated time section of reflected waves.